Effect of inhaled corticosteroids on bone mineral density in asthmatic children - Basavanagowda, Thanuja; Ramaraj, Savitha Mysore (International Journal of Contemporary Pediatrics, 2021)
Background: There is a rise in prevalence of asthma world-over. This study was undertaken as there are controversies regarding the effect of long term inhaled-corticosteroids (ICS) on bone mineral density (BMD). Methods: Asthmatic children belonging to 5-18 year age-group as per the global initiative for asthma guidelines (GINA) guidelines, who were on ICS for a minimum period of 6 months were studied. This study was conducted at a tertiary-care teaching hospital in Mysuru. 60 asthmatic children were compared with 60 non-asthmatic controls. Dual-energy x-ray absorptiometry at 6 sites was used for estimating the BMD and vitamin D levels were measured. Results: 0.771±0.114 g/cm2 was the mean total BMD among children on low dose ICS, while it was 0.613±0.192 and 0.564±0.104 g/cm2 respectively for those on medium and high dose ICS, with p value of 0.026. Children on low dose ICS did not have any impact on BMD, while 18.9% of those on medium and high dose ICS had a reduced total BMD. Trochanteric region was a useful predictor site for monitoring BMD in children on long term ICS with 38.7% and 68.9% being affected when on ICS for 6-12 months and more than 12 months respectively (p=0.018). Conclusions: The ICS of medium and high dose, for a duration of more than 6 months had a reduced total BMD. However, no effect was seen with low dose. Trochanter is a useful site for long term monitoring of BMD in children. There was no correlation between vitamin D levels and control of asthma.